1972
DOI: 10.1111/j.1752-1688.1972.tb05175.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Induced by an Internal Hydraulic Jump1

Abstract: The efficiency of an inverted internal hydraulic jump as a mixing and dispersion mechanism in an aquatic environment was examined. The flow considered was a two‐dimensional buoyant flow from a shallow channel over a sloping bottom into a deep reservoir. It could be seen that a rapidly varied flow associated with violent turbulent mixing occurred near the point of discharge if specific discharge conditions and downstream controls were met. Downstream from the mixing zone the flow was stably stratified. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The depth bj at the end of the jump, which was equal to ba>, was also measured. Since it was found that there is no entrainment in the jump region, the two subsequent depths b\ and bj are related by the Belanger type equation (17 (14) U\ being the mean (or depth averaged) velocity and Ae the mean density deficiency at the beginning of the surface jump. Knowing b\ and b\, F\ can be obtained from equation (13).…”
Section: («M/t/o)mentioning
confidence: 99%
See 3 more Smart Citations
“…The depth bj at the end of the jump, which was equal to ba>, was also measured. Since it was found that there is no entrainment in the jump region, the two subsequent depths b\ and bj are related by the Belanger type equation (17 (14) U\ being the mean (or depth averaged) velocity and Ae the mean density deficiency at the beginning of the surface jump. Knowing b\ and b\, F\ can be obtained from equation (13).…”
Section: («M/t/o)mentioning
confidence: 99%
“…But one finds in the literature a number of rather inconclusive (or even contradictory) statements regarding this surface jump. Some investigators indicate that under certain circumstances, the surface jumps entrain the ambient fluid whereas under certain other circumstances, the jumps are of the non-entraining type (14,16). If the jumps did indeed entrain the ambient fluid, then downstream sequent depth ratio is not a function (anymore) of only the upstream, Richardson (or densimetric Froude) number.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A solution similar to that above of the problem of contact of a buoyant surface jet with a pool of a water body based on introducing characteristic scales of the jet and direct solution of a simplified equation of momentum without changing to an equation of form (6) was proposed in [7] independently of the authors, and in this work the relation between variables h and q is not symmetric and the schemes of contact are not included, and therefore a comparison of the theoretical solution of Eq~ (6) with the experimental data, which is given in Fig. 4, is of great interest.…”
Section: Pamentioning
confidence: 99%